Dental flossing as a diagnostic method for proximal gingivitis: a validation study - Alessandra Pascotini GRELLMANN; Karla Zanini KANTORSKI; Thiago Machado ARDENGHI; Carlos Heitor Cunha MOREIRA; Cristiane Cademartori DANESI; Fabricio Batistin ZANATTA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
ABSTRACT This study evaluated the clinical diagnosis of proximal gingivitis by comparing two methods: dental flossing and the gingival bleeding index (GBI). One hundred subjects (aged at least 18 years, with 15% of positive proximal sites for GBI, without proximal attachment loss) were randomized into five evaluation protocols. Each protocol consisted of two assessments with a 10-minute interval between them: first GBI/second floss, first floss/second GBI, first GBI/second GBI, first tooth floss/second floss, and first gum floss-second floss. The dental floss was slid against the tooth surface (TF) and the gingival tissue (GF). The evaluated proximal sites should present teeth with established point of contact and probing depth ≤ 3mm. One trained and calibrated examiner performed all the assessments. The mean percentages of agreement and disagreement were calculated for the sites with gingival bleeding in both evaluation methods (GBI and flossing). The primary outcome was the percentage of disagreement between the assessments in the different protocols. The data were analyzed by one-way ANOVA, McNemar, chi-square and Tukey's post hoc tests, with a 5% significance level. When gingivitis was absent in the first assessment (negative GBI), bleeding was detected in the second assessment by TF and GF in 41.7% (p < 0.001) and 50.7% (p < 0.001) of the sites, respectively. In the absence of gingivitis in the second assessment (negative GBI), TF and GF detected bleeding in the first assessment in 38.9% (p = 0.004) and 58.3% (p < 0.001) of the sites, respectively. TF and GF appears to be a better diagnostic indicator of proximal gingivitis than GBI.